Implementasi Pendidikan Agama Islam Kontektual Berbasis Agroedukasi Terintegrasi Nilai-Nilai Islam di SMP Nurul Huda Merakurak - Amiruddin Marwan; Helco Dimas Prayoga (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe and analyze the implementation of contextual Islamic Religious Education (PAI) based on agro-education integrated with Islamic values at SMP Nurul Huda Merakurak. The background of this research is the need for a more practical and contextually relevant PAI learning model that aligns with students’ real-life environments, particularly in agrarian-based schools. This study employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation. The results show that PAI learning is directly integrated into agro- educational activities such as plant cultivation, environmental management, and character building through values such as trustworthiness (amanah), hard work, responsibility, and gratitude. PAI teachers play an active role in connecting Islamic teachings with agro-educational practices through contextual and reflective approaches. This research contributes to the development of a contextual and transformative PAI learning model that is relevant to local potential and students’ spiritual needs. The findings are expected to inspire other educational institutions in designing innovative PAI learning models based on environmental engagement and character development.